Pengelolaan Pembelajaran STEAM untuk Mengoptimalkan Perkembangan Anak Usia Dini - juwati juwati; Pardimin Pardimin (Universitas Sarjanawiyata Tamansiswa, 2022)
Research objectives include: analyzing steam learning management which includes; planning, organizing, implementing, supervising and evaluating to optimize early childhood development at ABA Ngoro-oro; analyze supporting factors and inhibitors in STEAM learning to optimize early childhood development at ABA Ngoro-oro; analyze steam learning management results to optimize early childhood development at ABA Ngoro-oro.This type of research is qualitative. Data collection techniques use interview, observation, and documentation techniques. Based on the results of the data analysis, it was concluded: In carrying out STEAM learning to optimize early childhood development in ABA Ngoro-oro, good management has been carried out which includes planning, organizing, implementing, and supervision and evaluation by involving all parties including principals, teachers, parents, committees and school supervisors; Supporting factors for competent human resources and good commitment, facilities and infrastructure that accommodate, loose parts media that can be taken from the surrounding environment for learning. The inhibitory factor is the existence of different teachers' understanding of steam learning management, loose parts media used do not match the ratio of the number of children; The results of steam learning management at ABA Ngoro-oro are able to optimize aspects of child development which include; aspects of the development of Moral Religious Values, Motor Physique, Cognitive, Language, Social Emotional and Artistic.